Analisis Perubahan Alih Fungsi Lahan Resapan Air Menjadi Lahan Terbangun di Kelurahan Hamadi - Alfredo H.S. Aronggear; Irja Tobawan Simbiak; Rasi K. Samosir (Fakultas Teknik Universitas Cenderawasih, 2026)
This study examines land-use transformation in Hamadi Rawa I, Jayapura City, focusing on the shift from water catchment to built-up land during 2015–2025. The research employs a mixed-methods approach, combining analysis of Google Earth imagery with interviews with community, government, and academic stakeholders. Findings show the catchment area shrank by 48% (from 17% to 8% of the total area), decreasing from 21.36 ha to 11.20 ha. The built-up area increased by 28.1%, from 70.78 ha to 90.67 ha, with residential development driving most of this growth (51.1%). Three spatial transformation patterns emerged: ecological fragmentation, linear service sector development, and concentric settlement patterns. Idle land was also identified as a phenomenon that damages ecological functions without providing a productive benefit. The conversion was driven by physical-natural factors (basin topography), economic factors (market proximity), socio-demographic factors (urbanization), and especially institutional factors. Customary land transactions outside state control created a governance dilemma between humanity and public order. The study recommends a proactive-collaborative approach with three key instruments: (1) Zero-Reclamation with Adaptive Permitting for stilt structures; (2) fiscal intervention using Idle Land Tax and Payment for Ecosystem Services; and (3) a Participatory Spatial Control Task Force integrating government and customary authorities (Ondoafi).